THE IMPLEMENTATION OF TEAM GAME TOURNAMENT (TGT) TYPE COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING MOTIVATION AND LEARNING ACHIEVEMENT - Nurul Hidayah; Abdullah Taman (Universitas Negeri Yogyakarta, 2017)
The objective of this research was improving learning motivation and learning achievement of XI Accounting 1 Students of SMK Negeri 1 Pengasih Academic Year 2016/2017 using Cooperative Learning Model Team Game Tournament (TGT) on the subject Accounting for Trading Company. This research was Classroom Action Research (CAR) collaborating with teacher in two cycle. Data collection technique used were questionnare, documentation, and test. Based on research result concluded that implementation of Cooperative Learning Model Team Games Tournament (TGT) could improve Learning Motivation and Learning Achievement of XI Accounting 1 student of SMK 1 Pengasih Academic Year 2016/2017 evidenced by improvement of motivation score and achievement score. Motivation questionnare result shown improvement of students’ learning motivation improved to 5.97% from cycle I of 72.41% increased to 78.13% in cycle II. Improvement of Accounting Learning Achievement calculated from the average score increase of 23.78% in first cycle and increased of 19.61% in the second cycle.Keywords: Cooperative Learning, Team Game Tournament, Learning Motivation, Learning Achievement